Victimological Study of Cases of Sexual Violence against Children in Buleleng Regency - Rai Yuliartini, Ni Putu; Gede Sudika Mangku, Dewa (Kertha Patrika, 2022)
This study aims to (1) describe and explain the role and position of children as victims of sexual violence in Buleleng Regency; and (2) describe and explain the rights and obligations of children as victims of sexual violence in Buleleng Regency. The type of research used is empirical legal research which is descriptive. The data and data sources used in this study are primary data and secondary data consisting of primary legal materials and secondary legal materials and. The data collection techniques used in this study are document study techniques, observations, and interviews. The sample determination technique used in this study is non probability sampling with the type of sample, namely purposive sample. Data processing and analysis techniques are carried out qualitatively. Based on the results of the study, it is known that (1) the role of children as victims of sexual violence in Buleleng Regency can be classified as latent or predisposed victims, provocative victims, and unrelated victims. Meanwhile, his position is that children are absolutely victims of sexual violence crimes; (2) the rights obtained by children as victims of sexual violence in Buleleng Regency are to receive treatment, protection, and recovery since the occurrence of the criminal act of sexual violence, while the obligation is to support all efforts and processes of fulfilling the rights obtained so that they can be fulfilled optimally.